Genetic Polymorphisms Affecting Tacrolimus Dose Requirements in Ghanaian Patients with End-Stage Renal Disease - Otabil, M.K. (University of Ghana, 2019)
Background: ESRD is the irreversible damage of a person’s kidney, affecting it normal physiological functions and rendering it fatal if not managed by dialysis or transplantation. In Ghana, ESRD is managed primarily by hemodialysis until the patient can afford kidney transplantation. However, transplants are accompanied with an immune response by the host immune system resulting in a high probability of organ rejection. Immunosuppressant dosing in combination with other immune regulatory medications are required to prevent transplant rejection. Tacrolimus is a first-line immunosuppressant; however, it has a narrow therapeutic range. Tacrolimus is a known substrate of CYP3A5, CYP3A4 enzymes and an efflux pump, P-glycoprotein. The differences in expression level of the substrates are a contributory factor to the individual variations of the pharmacokinetics of Tacrolimus. General Aim: To determine the genetic polymorphisms in CYP3A5, CYP3A4 and MDR1 genes in Ghanaian patients with End Stage Renal Disease. Method: This is a cross-sectional study that involved 87 ESRD patients, out of which 5 were transplant recipients and 82 were on dialysis. Clinical and demographic data were recorded and the genomic DNA isolated. Samples were genotyped for specific SNPs in CYP3A5*3 6986 A>G rs776746, CYP3A4*1B -290 A>G rs2740574, MDR1_Ex12 1236 C˃T rs1128503, MDR1_Ex26 3435 C>T rs1045642, MDR1_Ex21 2677 G>A rs2032582 and MDR1_Ex21 2677 G˃T rs2032582 using PCR-RFLP. The genetic frequencies of the transplant recipients were analyzed against the patients’ Tacrolimus dose and trough levels. Outcome: The mean age of study participants was recorded as 46 years ±14.39. The etiologies of ESRD were mostly hypertension and diabetes. The frequency of CYP3A5*3 (6986 A˃G) genes expressed showed that 4.6% were mutant. This mutant gene was expressed only among the dialysis patients. The frequency of CYP3A4*1B (-290 A˃G) genes expressed showed that 79.31% were mutant, out of which 80% were from the transplant recipients. A wild-type genotypic frequency of 100% was recorded in the participants for the MDR1_Ex12 (1236 C˃T) gene. Also, a 100% wild-type genotypic frequency was recorded in the participants for the MDR1_Ex21 (2677 G˃A) genes. No homozygous mutant genotype was expressed for MDR1_Ex21 (2677 G˃T) genes, however, 1.15% expressed the heterozygous genotype. None of the participants expressed the mutant genotype TT which affects the level of expressed P-glycoprotein in the transmembrane region of cells. The frequency of MDR1_Ex26 (3435 C˃T) genes expressed showed that 1.15% were mutant genotype. From the Tacrolimus trough level and genotype analysis, four transplant recipients expressing the homozygous variant CYP3A4*1B/*1B recorded significantly lower Tacrolimus trough level (average of 5.95± 1.8 ng/ml) compared to the fifth recipient (10.3ng/ml). There was no clear correlation between the expressed genes of the MDR1 haplotype genes and Tacrolimus trough level.
MPhil. Pharmacology
Keywords: End-Stage Renal Disease; Tacrolimus Dose